A new species of Rhinophis Hemprich, 1820 (Serpentes: Uropeltidae) from southwestern Sri Lanka - Gower, David J. (Zootaxa, 2020)
A new species of the uropeltid snake genus Rhinophis Hemprich, 1820 is described from near Balangoda, southwestern Sri Lanka. Rhinophis mendisi sp. nov. superficially resembles R. homolepis (Hemprich, 1820) in colour pattern and in its prominent, conical tail shield, but differs from that species in having far fewer ventrals (159–177, n = 13 versus > 195 in the types of R. homolepis and its subjective junior synonym R. gerrardi). The five type specimens and one of the referred specimens of the new species were collected probably between 1894 and 1925, and the only known additional, referred specimens (n = 8) were collected from within ca. 30 km of the type locality in 1972. A lectotype is designated for Mitylia gerrardi Gray, 1858, a subjective junior synonym of R. homolepis.